1997
DOI: 10.1021/ed074p819
|View full text |Cite
|
Sign up to set email alerts
|

Students' Misconceptions in Electrochemistry Regarding Current Flow in Electrolyte Solutions and the Salt Bridge

Abstract: Several researchers have documented students' misconceptions in electrochemistry. One reason for the interest in studying electrochemistry is that surveys of students and teachers suggest that students find this topic difficult and research confirms that students' beliefs about problem complexity affect their performance and learning. Several articles have promoted pedagogical suggestions or opinions about more effective mehods of teaching electrochemistry; but few, if any, of these have actually been tested.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
112
1
11

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(132 citation statements)
references
References 16 publications
8
112
1
11
Order By: Relevance
“…One reason why students may have difficulty with the concepts of diffusion, osmosis and active transport is that these concepts require students to visualize and think about chemical processes at the molecular level (Johnstone & Mahmoud, 1980;Friedler et al, 1987;Westbrook & Marek, 1991). Studies have shown that instruction involving computer animations can facilitate the students thinking about chemical processes at the molecular level (Williamson & Abraham, 1995;Russel et al, 1997;Sanger & Greenbowe, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…One reason why students may have difficulty with the concepts of diffusion, osmosis and active transport is that these concepts require students to visualize and think about chemical processes at the molecular level (Johnstone & Mahmoud, 1980;Friedler et al, 1987;Westbrook & Marek, 1991). Studies have shown that instruction involving computer animations can facilitate the students thinking about chemical processes at the molecular level (Williamson & Abraham, 1995;Russel et al, 1997;Sanger & Greenbowe, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies (Bojczuk, 1982;Lee & Kamisah, 2010;Lin et al, 2002;Roziah, 2005) showed that the topic is difficult to learn because the concepts are abstract. Students often encounter misconceptions in the learning of this topic (Garnett & Hackling 1993;Garnett & Treagust 1992;Garnett et al 1995;Lee & Mohammad Yusof 2009;Lee 2008;Lin et al 2002;Sanger & Greenbowe 1997a;Sanger & Greenbowe 1997b). Macroscopically, students need to study the concepts of electrolytes and non-electrolytes, the electrolysis process and voltaic cells.…”
Section: Study Of Electrochemistrymentioning
confidence: 99%
“…Besides that, they also need to transform the process into chemical formulae and equations symbolically. Students face difficulties in understanding the abstract chemical processes especially on microscopic and symbolic levels (Garnett & Hackling 1993;Garnett & Treagust 1992;Garnett et al 1995;Lee & Mohammad Yusof 2009;Lee 2008;Lin et al 2002;Sanger & Greenbowe 1997a;Sanger & Greenbowe 1997b). Generally, some common misconceptions or problems faced by students in learning Electrochemistry are: (1) students are always confused between the flow of current in the conductors and in the electrolytes; (2) they cannot identify the anode and cathode/positive and negative terminal in the cell; (3) they cannot describe and explain the process happening at the anode and cathode; (4) they mix up the oxidation and reduction process at the electrodes; and (5) they are unclear about the concept of electrolyte (Lee & Mohamad Yusof, 2009;Lee, 2008).…”
Section: Study Of Electrochemistrymentioning
confidence: 99%
“…Research in chemistry education has shown that students often have difficulty in understanding chemistry concepts due to their abstract nature and many attempts have been made by researchers to assist students' learning by identifying the difficulties experienced by students and possible solutions to overcome this problem Greenbowe, 1997a and1997b;Niaz & Chacon, 2003;Ozmen, 2004;Ozkaya et al, 2006). There are three levels of representation of chemical phenomena: macroscopic, sub-microscopic and symbolic (Treagust et al, 2003).…”
Section: Introductionmentioning
confidence: 99%